Effect of the Transition Metal Elements on the Relaxation Times in the Agar Solutions - ASKIN, MUZAFFER (Asian Journal of Chemistry, 2010)
In this study, the relaxation times of T1 spin-lattice and T2 spinspin are measured by adding the ions such as Mn2+, Cr3+, Fe3+, Ni2+ and Cu2+ in various concentrations to the different concentration of agar solution. The measurement are carried out by using a FT-NMR spectrometer working at the proton resonance 60 MHz at the room temperature. T1-measurement is realized by the technique of the Inversion Recovery (IR) and the T2-measurement by that of the Spin-Echo (SE). It is found that the variation of the 1/T1 and 1/T2 with respect to the ion concentration is linear for each agar concentration. Furthermore, the effect of the each ion in favour of the contribution to the relaxation is evaluated depending on ε, the relaxation-enhancement parameter of the proton added to a solution.